Pembuatan Media Promosi Lewat Konten Feed Instagram Untuk Menarik Minat Beli Pada Bumi Asih Travel di Trenggalek - Setyowati, Sulis; Khabibah, Umi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Rapid advances in digital technology have changed the way promotions are conducted in the modern era. Bumi Asih Travel, a domestic travel agency, previously relied on WhatsApp Stories as a promotional medium, which limited its reach and effectiveness. Although they had an Instagram account, it was used for personal purposes and did not display promotional content in a professional manner. This study aims to develop an Instagram account with attractive feed content to increase purchasing interest and expand market reach. This study employs an action research approach. CorelDraw design software was used to create the Instagram feed content for Bumi Asih Travel. Data collection techniques included observation, interviews, documentation, and questionnaires. Purposive sampling was used in the design test with informants consisting of 2 design experts, 2 marketing experts, 1 Bumi Asih Travel business owner, and 10 potential customers. Data was analyzed using qualitative descriptive methods. The study results show that the promotional media through Instagram feed content created and published on the new Bumi Asih Travel account achieved an average score of 82% for attention, 83.34% for interest, 81.34% for desire, and 86.67% for action. All these results are categorized as “very good.” (≥81%). These results indicate that Instagram feed content is effective in attracting attention, generating interest, encouraging desire, and prompting purchase actions. From these results, it can be concluded that Instagram feed content is proven to be effective as a promotional medium and capable of increasing purchasing interest in Bumi Asih Travel. It is recommended that Bumi Asih Travel maintain a more active and professional presence on this platform.